ANALISIS KUALITAS PELAYANAN, KEPERCAYAAN DAN KETEPATAN WAKTU TERHADAP KEPUASAN PELANGGAN PT. PILAR PRIMA NUSANTARA (J&T EXPRESS) DELANGGU - William Arbiansyah Pasaribu; Bambang Mursito; Djumali Djumali (JURNAL ILMIAH EDUNOMIKA, 2021)
Business people experience very tough competition. Every shipping business actor is required to be sensitive to any changes that occur and prioritize customer satisfaction as the main goal. This study aims to identify and explain customer satisfaction in terms of service quality, trustworthiness, and timeliness of delivery of J&T Express Delanggu customers. The research sampling technique used accidental sampling of 100 consumers with multiple linear regression method. The results of this study are service quality, trustworthiness, and punctuality have a significant effect on customer satisfaction J&T Express Delanggu. Partially each variable, namely service quality, trustworthiness, and timeliness have a significant effect on customer satisfaction at J&T Express Delanggu. Customer satisfaction variables can be explained by the variable product quality, brand image and service by 31.7% and others are influenced by other variables. Keywords: purchase decisions, service quality, trustworthiness, and timeliness